The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 09: the False Nun - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 09: the False$1! =(B" is part of Giacomo Casanova's massive autobiography written in French during the late 18th century. This Venetian adventurer's unfinished memoir spans twelve volumes and 3,500 pages, chronicling his extraordinary life from birth through 1774. The original manuscript endured a fascinating journey$1 (Bcensored, mistranslated, and pirated across Europe for over a century before the unexpurgated version finally emerged in the 1960s. This volume captures another chapter of Casanova's legendary adventures through aristocratic Europe. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2004-12-10
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography